Polymorphism of 5’UTR myostatin gene indel (g.1256/TTTTA) and its association with body weight in Boerka crossbred goat - Ismail, R.; Handiwirawan, E.; Elieser, S.; Jakaria, J. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
This study aimed to identify the variation of 5’UTR Myostatin (MSTN) gene and its association to body weight in Boer, Kacang, and Boerka goats. DNA samples were obtained from 149 heads of the goats from the Indonesian Goat Research Center, Sungei Putih, North Sumatera. Polymorphism identification was conducted by direct sequencing and PCR-RFLP with DraI as the restriction enzyme for indel g.1256/TTTTA. Analysis of variance for body weight was carried out using the General Linear Model (GLM). The 5’UTR MSTN gene|DraI was monomorphic in Kacang but polymorphic in Boer and Boerka. Genotype frequencies for Boer 0.40(AA), 0.43(AB), 0.17(BB); Kacang 1.00(AA); Boerka 0.53(AA), 0.37(AB), 0.10(BB). The allele frequencies for Boer 0.62(A), 0.38(B); Kacang 1.00(A); Boerka 0.72(A), 0.28(B), respectively. AB was the most frequent genotype among Boer, but AA was the most frequent in Kacang and Boerka. Indel g.1256/TTTTA has a significant effect (P<0.05) only on birth weight (BW) of Boer, but no significant effect on other bodyweight parameters both in Boer and Boerka.AA genotype has the highest BW (P<0.05) than AB, but it’s not significantly different from BB. Indel g.1256/TTTTA could be used as a genetic marker for the birth weight of Boer but not in Boerka goats.